Potomac River Basin water supply; an interim report. - United States. Army. Corps of Engineers. ([Baltimore?], 1973)
"Prepared by Department of the Army, Baltimore District, Corps of Engineers, for Northeastern United States water supply study, Department of the Army, North Atlantic Division, Corp of Engineers." Includes bibliographies. v. 1. Main report.--v. 2. Summary statement of findings and recommendations. Mode of access: Internet.